Clean Development Mechanism dan Upaya Reforestasi di Indonesia - Hasanah, Uswatun; Ahmad, Mubariq (Jurnal Ekonomi dan Pembangunan Indonesia, 2003)
International environmental issue recently plays important role in world economic development and their sustainability.This trans-boundary environmental problem requires a global responsibility, especially for forest well endowed countries like Indonesia to hold main role to support the environmental sustainability. We apply cost benefit analysis on carbon trade using Clean Mechanism Development to show its significant contribution on green forestry program. This paper gives us the picture of Indonesia's forestry, the beneficial of forest's project and the finding of global responsibilities to make a better for mankind. Our perspective about the utility of forest is very important to determine the decision we choose.